Review on essential oils, chemical composition, extraction, and utilization of some conifers in Northwestern Himalayas - Bhardwaj, Kanchan; Islam, Muhammad Torequl; Jayasena, Vijay; Sharma, Bechan; Sharma, Somesh; Sharma, Pankaj; Kuča, Kamil; Bhardwaj, Prerna (Phytotherapy research, 2020)
Essential oils (EOs) are regarded as alternative therapeutic agents for many diseases. In phytotherapy research areas, it is now well reported that conifers are the rich source of EOs. This review aims to update information on the biological sources and the best extraction processes of the significant constituents along with the traditional and therapeutic properties of the EOs from selected conifers of Himachal Pradesh, Northwestern Himalaya. In the present review, ten conifer species of high values have been selected. Results from several studies suggest that the conifers contain monoterpenes, sesquiterpenes, diterpenes, ketones, alcohols, and esters, which are used in medicines, food products, and cosmetics as well as other commercial and industrial products. Traditionally, the EOs from the conifers have been reported to be used against fever, cough, bronchitis, skin diseases, gastrointestinal disorders, and asthma. The pharmacological studies suggest that these EOs can be used as antirheumatic, antiseptic, antispasmodic, anticancer, anti-inflammatory, antitoxic, aphrodisiac, and astringent agents. It is, therefore, concluded that the EOs from the conifers might be one of the promising tools for the treatment of various diseases. Extensive research is required to ascertain the efficacy of the EOs from unstudied conifers.
Keywords: Himalayas; oleje prchavé; Tracheophyta; ethnobotanical uses; lidé; conifers; medicinal properties; Oils, Volatile; Humans; cévnaté rostliny; essential oils